CLINICAL IMPLICATION OF ASSESSING QUANTITATIVE PLASMA CONCENTRATIONS OF ANTIHYPERTENSIVE DRUGS. (April 2021) - Peeters-Kalicharan, Laura; Feyz, Lida; Daemen, Joost; Van Gelder, Teun; Koch, Birgit; Versmissen, Jorie
Abstract : Objective: Dried blood spot (DBS) analysis is a novel analytical method for therapeutic drug monitoring (TDM) to identify non-adherence to antihypertensive drugs. This study was conducted to evaluate the clinical applicability of measuring drug concentrations of eight antihypertensive drugs, using DBS and venipuncture. Furthermore, this study aimed to provide more insight into the between-patient variability in drug concentrations. Figure. No caption available. Design and method: In a previous study a TDM method for eight antihypertensive drugs and four of their metabolites (table 1) was validated in patients assumed to be adherent. The present data was retrieved from this validation study. False negative values from DBS compared to a venipuncture were determined to assess drug adherence. A Generalized Estimating Equation (GEE) was used to assess the influence of covariates including gender, dose, age, weight, and the time interval between drug intake and sampling on the Cplasma (drug concentration in plasma). Results: A total of 135 patients (mean age of 59 ± 12 years, 59% male) were included. The number of samples per drug ranged from 38 (enalaprilate) to 85 (hydrochlorothiazide). When drug concentrations from DBS and plasma were compared, no real false negative values were found. A high variability in Cplasma between patients was observed, especially at peak concentrations with a fold change reaching from 2.3 (canrenone) to 35.2 (losartan-carboxylic acid) (table 1). The time of intake was significantly related to the height of the Cplasma in 7 of the 8 measured drugs with a p-value < 0.05 with the exception of hydrochlorothiazide, but the influence of dose, weight, age and sex on drug levels differed largely between the measured drugs. Conclusions: DBS is a reliable and convenient method to assess non-adherence to antihypertensive drugs in clinical practice. The Cplasma of the eight antihypertensive drugs in this study show a large inter-individual difference and therefore low plasma concentrations do not necessarily mean non-adherence. Non-adherence can only be confirmed if drug levels are undetectable, i.e. values below the lower limit of detection.